Handbuch kommunikationswissenschaftliche Erinnerungsforschung - Pentzold, Christian; Lohmeier, Christine (De Gruyter Reference, 2023)
This handbook provides a comprehensive overview of the principles, perspectives, and main emphases of studying processes of communicative remembering and media memory. Its chapters analyze the field of communication memory studies and link it to complementary approaches from the social sciences, the humanities, and cultural studies.